Theory Versus Practice in Risk Analysis: An Empirical Study: A Comment. - Fishburn, Peter C. (The Accounting Review, 1976)
Abstract The article presents comments of the author on the article "Theory Versus Practice in Risk Analysis: An Empirical Study," by Willis R. Greer. In his Greer, claimed to show a conflict between utility theory and actual decisions made by representatives of twenty-seven Fortune 500 firms. Although the article provided an interesting analysis of firms' decisions, it seems misleading in two important respects. First, the hypothesis tested by Greer is quite different than the hypothesis that he suggested he was testing. Second in contrast to his claim of a substantial conflict between the decision processes used by actual decision makers and existing utility theory, the data give fairly good support to the counterclaim that the decision makers in his study tend to be expected utility maximizers. The latter point already has been discussed by scholar C.G. Hoskins and Greer and scholar Ted D. Skekel. More is said about this later in this comment. The interpretative problems with Greer's original article appear to arise from the author's conception of "existing utility theory." This conception is tied to a mean-standard deviation trade off model.